2003
DOI: 10.1046/j.1524-475x.2003.11105.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 and a synthetic peptide containing its actin‐binding domain promote dermal wound repair in db/db diabetic mice and in aged mice

Abstract: Impaired wound healing is a problem for immobilized patients, diabetics, and the elderly. Thymosin beta 4 has previously been found to promote dermal and corneal repair in normal rats. Here we report that thymosin beta 4 was also active in accelerating wound repair in full-thickness dermal wounds in both db/db diabetic and aged mice. We found that thymosin beta 4 in either phosphate-buffered saline or a hydrogel formulation is active in promoting dermal wound repair in normal rats. In diabetic mice, where heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 33 publications
3
97
0
Order By: Relevance
“…Actin is essential for cell division, cell movement, phagocytosis and differentiation. In addition, the central actin-binding site in thymosin b4 is required for its angiogenic [7] and wound-healing activity [8,9], suggesting that its interaction with actin is functionally important beyond sequestration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Actin is essential for cell division, cell movement, phagocytosis and differentiation. In addition, the central actin-binding site in thymosin b4 is required for its angiogenic [7] and wound-healing activity [8,9], suggesting that its interaction with actin is functionally important beyond sequestration [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the extracellular space, thymosin β 4 participates in several physiological processes, e.g. angiogenesis (Grant et al, 1995;Malinda et al, 1997;Philp et al, 2003b), wound healing (Malinda et al, 1999;Sosne et al, 2001;Sosne et al, 2002;Philp et al, 2003a) and regulation of inflammation (Sosne et al, 2001;Sosne et al, 2002). We have recently shown that it also serves as a specific glutaminyl substrate of transglutaminases (Huff et al, 1999) which crosslink thymosin β 4 released from stimulated human platelets to fibrin and collagen .…”
Section: Introductionmentioning
confidence: 99%
“…Thymosin β4 has shown promising efficacy in animal models of various diseases, such as myocardial infarction, dermal wounds, multiple sclerosis, sepsis and endotoxic shock (12,20,(28)(29)(30)(31). However, to the best of our knowledge, there have been no reports concerning thymosin β4 in the treatment of acute pancreatitis until now.…”
Section: Discussionmentioning
confidence: 99%